2015
DOI: 10.4085/1002103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Fidelity Cardiopulmonary Resuscitation (CPR) Simulation on Athletic Training Student Knowledge, Confidence, Emotions, and Experiences

Abstract: Context High-fidelity simulation is widely used in healthcare for the training and professional education of students though literature of its application to athletic training education remains sparse. Objective This research attempts to address a wide-range of data. This includes athletic training student knowledge acquisition from high-fidelity simulation, effects on student confidence, emotional responses, and reports of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 33 publications
4
26
0
5
Order By: Relevance
“…There is documentation 12,14,33 that both simulations and case studies have positive outcomes on learning in athletic training education, which was also supported by the current study. The current study found participants in both HS and CBL groups experienced an increase in knowledge, preference, and practice related to EHS that was also retained at the 6-week follow-up period.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There is documentation 12,14,33 that both simulations and case studies have positive outcomes on learning in athletic training education, which was also supported by the current study. The current study found participants in both HS and CBL groups experienced an increase in knowledge, preference, and practice related to EHS that was also retained at the 6-week follow-up period.…”
Section: Discussionsupporting
confidence: 84%
“…Researchers in athletic training have examined the effectiveness of either SPs or high-fidelity simulations on educational outcomes such as confidence, clinical skills, and knowledge. 11,20,28,[31][32][33][34] Therefore, the purpose of this study was to compare 2 learning strategies, CBL using a case study and HS using a SP and a rectal mannequin task trainer, to evaluate the pedagogic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo realizado nos Estados Unidos com 90 estudantes de enfermagem, com objetivo de descrever o uso de uma estratégia educacional envolvendo simulação para preparar estudantes de enfermagem a lidar com situações de emergência, foi observado que 95% dos estudantes recomendaram a simulação como estratégia educativa, pois concordam que a simulação ajuda a aumentar o conhecimento e a confiança em lidar com uma emergência clínica [44]. Outra vantagem apontada pelos estudantes é que ela permite que os estudantes possam praticar os conhecimentos teóricos adquiridos com feedback instantâneo, tudo isso em um ambiente controlado sem promover riscos ao paciente [14,45,46]. Sobre o feedback e debriefing após os cenários de simulação, estudo aponta que as emoções devem consideradas, principalmente por causa do impacto emocional na aprendizagem e no desempenho do estudante [33].…”
Section: Discussionunclassified
“…Sahu & Lata (2010) telah menjelaskan bahwa salah satu keuntungan dari metode ini adalah dapat meningkatkan pengetahuan peserta pelatihan melalui proses berpikir kritis terhadap suatu permasalahan yang disajikan pada proses simulasi. Tivener & Gloe (2015) juga menguatkan bahwa adanya permasalahan yang diberikan pada proses simulasi juga akan membantu untuk membuat peserta melakukan analisis permasalahan yang akan berujung pada peningkatan nilai pengetahuan yang dimiliki oleh peserta.…”
Section: Pembahasanunclassified
“…Proses pelatihan dengan metode ini juga akan memberikan kesempatan pada responden untuk melakukan tindakan RJP dengan pengawasan langsung dari instruktur dan adanya proses bimbingan langsung dari instruktur serta proses evaluasi hasil pembelajaran di akhir sesi pertemuan. Proses yang dilakukan ini juga akan memberikan kemudahan kepada peserta pelatihan dalam menguasai keterampilan dalam melakukan tindakan RJP (Tivener & Gloe, 2015).…”
Section: Pembahasanunclassified